2020
DOI: 10.1002/humu.24150
|View full text |Cite|
|
Sign up to set email alerts
|

New clinical and molecular evidence linking mutations in ARSG to Usher syndrome type IV

Abstract: In murine and canine animal models, mutations in the Arylsulfatase G gene (ARSG) cause a particular lysosomal storage disorder characterized by neurological phenotypes. Recently, two variants in the same gene were found to be associated with an atypical form of Usher syndrome in humans, leading to visual and auditory impairment without the involvement of the central nervous system. In this study, we identified three novel pathogenic variants in ARSG, which segregated recessively with the disease in two familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…Consequently, CEP250 is now categorized as an USH-like gene. Recently, three studies with comparable cases identified ARSG mutations in atypical USH patients, designated as USH type 4 [128][129][130]. This appears to be a robust new candidate gene responsible for the disease, and ARSG should be included in upcoming genetic screenings.…”
Section: Other Related Genesmentioning
confidence: 99%
“…Consequently, CEP250 is now categorized as an USH-like gene. Recently, three studies with comparable cases identified ARSG mutations in atypical USH patients, designated as USH type 4 [128][129][130]. This appears to be a robust new candidate gene responsible for the disease, and ARSG should be included in upcoming genetic screenings.…”
Section: Other Related Genesmentioning
confidence: 99%
“…Specifically, SGSH removes the sulfate group from N-Sulfoglucosamine by hydrolysis to produce D-Glucosamine [15]; when SGSH activity is absent, subsequent steps in the HS degradation pathway (e.g., NAGLU-mediated acetylglucosaminidase activity impaired in MPS IIIB, HGSNAT-mediated acetyltransferase activity which is impaired in MPS IIIC, or GNS-mediated sulfatase activity in MPS IIID) cannot occur. Another subtype, putatively referred to as MPS IIIE, is thought to result from arylsulfatase G (ARSG) dysfunction, but this has only been observed in animal models [16,17] and has yet to be described in a human patient (most ARSG mutations are instead associated with Usher syndrome type 4 [OMIM 6181440]) [18][19][20][21]. MPS IIIA, the most common of the MPS III subtypes [22], tends to exhibit greater clinical severity and progresses more rapidly than other MPS III subtypes [10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Khateb et al reported mutations in this gene in a family with “atypical” Usher [ 111 ]. Subsequently, it has been described as Usher 4, but this new entity has not been widely reported and accepted to date [ 111 , 112 , 113 , 114 ]. The introduction of a new clinical type USH4 is not widely accepted, and further studies are required to confirm these hypotheses.…”
Section: Genetics Of Ushmentioning
confidence: 99%